Novel p-Hydroxybenzoic Acid Derivative Isolated from Bacopa procumbens and Its Antibacterial Activity - Elizabeth Vargas-Anaya; Alejandro Zamilpa; Manasés González-Cortazar; Blanca Eda Domínguez-Mendoza; Ma. Dolores Pérez-García; Minerva Rosas Morales; Ada María Ríos Cortés; Valentin López Gayou (Antibiotics)
Background/Objectives: Antimicrobial resistance represents a critical global health challenge that has been exacerbated by the significant decline in antibiotic development. Natural product-based drugs, particularly plant-derived phenolic compounds, offer promising alternatives to conventional antibiotics. This study aimed to isolate and characterize a novel phenolic compound from Bacopa procumbens, a Mexican perennial repent plant that is widespread in the Mexican valley and produces a variety of saponins, gastrodin derivatives, and phenolic acids, and to evaluate its antibacterial potential against clinically relevant pathogens. Methods: The hydroalcoholic extraction of B. procumbens was followed by liquid–liquid partitioning with ethyl acetate. The resulting fraction underwent chromatographic separation and purification. The structural elucidation of the isolated compound was performed using thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC), mass spectrometry (MS-EI), and nuclear magnetic resonance (NMR) techniques. Antimicrobial activity was assessed via a microdilution assay against five bacterial strains, including drug-resistant Staphylococcus species and Gram-negative pathogens. Results: A novel phenolic compound, 5-(p-hydroxybenzoyl) shikimic acid (5pHSA), was isolated and characterized. The compound demonstrated moderate antibacterial activity against methicillin-resistant Staphylococcus haemolyticus and Escherichia coli (minimum inhibitory concentration (MIC) = 100 μg/mL) but showed limited efficacy against Staphylococcus aureus, MRSA, and Klebsiella pneumoniae (MIC > 100 μg/mL). Comparative analysis with the previously isolated compound ProcumGastrodin A revealed structure–activity relationships where the higher lipophilicity of PG-A was correlated with enhanced antimicrobial activity. Conclusions: This study establishes 5pHSA as a novel phenolic compound with moderate antibacterial properties. The findings highlight the importance of molecular polarity and structural complexity in determining antimicrobial efficacy, offering valuable insights into the development of phenolic, acid-based antimicrobial agents to address the growing challenge of antimicrobial resistance.